2018
DOI: 10.1007/s00261-018-1646-5
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoral tissue on preoperative imaging reveals microvascular invasion in hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: The two peritumoral imaging features are significantly associated with MVI. The two features highly suggest MVI only when present with a high false negative rate. Promotion of their diagnostic efficiency can be a worthwhile task for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 36 publications
6
38
0
Order By: Relevance
“…PT-E can reflect hemodynamic perfusion changes of HCC with MVI [11], which is useful for predicting MVI of HCC and the risk of ER. Our study found that PT-E was a significant indicator of ER, which was similar to previous reports [13, 14, 16, 3032]. However, the prediction accuracy was low; in our study, the AUC of PT-E was only 0.61 (95% CI, 0.47 to 0.74).…”
Section: Discussionsupporting
confidence: 89%
“…PT-E can reflect hemodynamic perfusion changes of HCC with MVI [11], which is useful for predicting MVI of HCC and the risk of ER. Our study found that PT-E was a significant indicator of ER, which was similar to previous reports [13, 14, 16, 3032]. However, the prediction accuracy was low; in our study, the AUC of PT-E was only 0.61 (95% CI, 0.47 to 0.74).…”
Section: Discussionsupporting
confidence: 89%
“…A recent meta-analysis focused on the association between peri-tumoral MRI features and MVI, which revealed a significant association between MVI and peri-tumoral enhancement and peritumoral hypointensity on hepatobiliary-phase MRIs. However, the diagnostic accuracy analysis of this previous study showed relatively high specificity (0.90-0.94), low sensitivity (0.29-0.40) in assessing MVI (31). In another study, three radiomic models were built by extracting radiomic features from both intra-tumoral and peri-tumoral regions of Gd-EOB-DTPA-enhanced MRI images, which yielded an AUC value of 0.83 in predicting MVI (23).…”
Section: Discussionmentioning
confidence: 70%
“…Previously, various research on preoperative identifying MVI by imaging modalities has been mainly focused on inside tumor features. In recent years, imaging features of peri-tumoral area have been proved to be more accurate (18), since peri-tumoral tissue is the first area to be invaded by MVI (31). A high level of placental growth factor (PlGF) and expression of vascular endothelial growth factor receptor (VEGFR-1) in peri-tumoral tissue has been associated with peri-tumoral MVI pathological angiogenesis and potential vascular invasion (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] CECT [58] also demonstrated that a combination of two or more of the following; arterial peritumoral enhancement, irregular tumor margin, and peritumoral hypointensity on hepatobiliary phase, can be used as a preoperative imaging biomarker for predicting MVI, with specificity > 90%. Hu et al [59] also reported in a systemic review and meta-analysis that peritumoral enhancement and peritumoral hypointensity on hepatobiliary phase were highly specific (90%-94%) but low sensitive findings (29%-40%) for predicting MVI.…”
Section: Refmentioning
confidence: 97%